Cyanide and cassava breeding - Mahungu, N.; Hahn, S.K.; Chheda, H.R. (1994)
Cassava (Manihot esculenta Crantz) contains cyanogenic glucosides which lead to the release of hydrogen cyanide (HCN) after hydrolysis. A study carried out using six cassava populations revealed that the broad-sense heritability for HCN was relatively low at 34.58 and 32.18 percent in roots and leaves respectively. Relationships between HCN in roots and leaves and twenty other cassava characters were examined. None of the characters was found significantly related to cyanide content in either leaf or root, except for a negative genotypic association between root HCN and plant height at harvest in some populations. Also a weak positive genotypic correlation (r = 0.20 and 0.26) between root yield and root HCN was found only in two populations while the same two traits had negative or no correlation in the other four populations. It was concluded that the presence of HCN in cassava does not confer on the plants a useful survival or protective mechanism except possibly to some wild animals. The study also indicated that in most breeding populations, it is possible to develop high-yielding cassava genotypes with low cyanide content; Cyanides; Hydrocyanic acid; Agronomic characters; Plant breeding; Nigeria Manihot esculenta; Cianuros; Acido cianhídrico; Características agronómicas; Fitomejoramiento; Nigeria Cassava; Yuca; Fisiología y bioquímica de la planta; Articles in proceedings; Artículos en memorias; Genética vegetaly fitomejoramiento Plant physiology and biochemistry; Plant genetics and breeding.